STUDI PENGELOLAAN AKTIVITAS TENAGA PENJUALAN SEBAGAI USAHA PENINGKATAN KINERJA TENAGA PENJUALAN - Jatmiko, Robby (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2017)
The study aims to find the proper management of sales force activitiesas an effort to improve the performance of salespeople. The proposed researchproblem refers to the research gap of previous research. The formulation of theproblem in this research is how to improve the performance of sales force so thatsales performance can reach the target. Furthermore, to answer the problemdeveloped a modeling and five hypotheses have been formulated in this study.The sampling technique used is the census method. The sample of this studyamounted to 109 respondents, where the respondents are the salespeople of PT.Tempo Scan Pasific in Central Java and Yogyakarta. The data analysis toolused is Structural Equation Modeling (SEM) in AMOS 4.01 program. Theresults of this research data analysis show the model and research results can bereceived well. And then the results of this study prove that the influence of salesarea design on the intensity of sales force activity is positive and significant.The influence of work motivation of sales force to the intensity of sales forceactivity is positive and significant. The effect of sales area design onsalesperson performance is positive and significant. The influence of themotivation of the sales worker's performance on the performance of the salesforce is positive and significant. The effect of the intensity of salespeople activityon salesperson performance is positive and significant.